Analisis Tingkat Kepuasan Anggota Simpan Pinjam Menggunakan Metode Customer Satisfaction Index pada UPK Syariah Tujuah Sarumpun Ampek Angkek - Leli Febriani; Tartila Devy (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This research was motivated by issues affecting member satisfaction, such as operational delays and slow disbursement of funds. This study aims to analyze the level of member satisfaction with UPK services using the Customer Satisfaction Index (CSI) approach. This study employed quantitative and qualitative descriptive methods, using a questionnaire based on the SERVQUAL model, which covers five service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The study sample consisted of 80 respondents from a total population of 399 active members. Data analysis used the CSI formula, which measures the level of importance and satisfaction for each indicator. Data were analyzed using Microsoft Excel and tested for validity and reliability using SPSS. The calculation results indicate that the CSI score is in the "satisfactory" category, but service quality is not evenly distributed across all dimensions. The first dimension that is not yet met is responsiveness, particularly in terms of the speed of employee responses to member requests and questions. The second dimension, reliability, concerns the issue of employee timeliness in providing services to members. These findings indicate the need to improve employee professionalism and the institution’s operational efficiency to increase member loyalty. This research is expected to provide strategic considerations for UPK managers in formulating better and more sustainable service policies.